2004
DOI: 10.1111/j.1439-0418.2004.00897.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of cross‐resistance in pyrethroid‐selected populations of Helicoverpa armigera Hübner (Lep., Noctuidae) from India

Abstract: In Helicoverpa armigera, withdrawal of selection pressure resulted in a two-to fourfold increase in susceptibility to synthetic pyrethroids and continuous selection enhanced the resistance level by four-to fivefold to the respective pyrethroids at the end of the 14th generation. Populations selected for resistance to one pyrethroid showed positive cross-resistance to all other pyrethroids, but no cross-resistance to endosulfan and thiodicarb. There was a significant increase in mixed-function oxidase activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 21 publications
0
22
0
1
Order By: Relevance
“…It also attacks more than 100 crops (Talukder and Howse 1994). Both H. armigera and S. litura have developed resistance against synthetic pesticides (Kumar and Reghupathy 2001;Ramasubramaniam and Regupathy 2004). Mosquitoes are responsible for spreading diseases like malaria, Japanese encephalitis, yellow fever, dengue and filariasis.…”
Section: Introductionmentioning
confidence: 99%
“…It also attacks more than 100 crops (Talukder and Howse 1994). Both H. armigera and S. litura have developed resistance against synthetic pesticides (Kumar and Reghupathy 2001;Ramasubramaniam and Regupathy 2004). Mosquitoes are responsible for spreading diseases like malaria, Japanese encephalitis, yellow fever, dengue and filariasis.…”
Section: Introductionmentioning
confidence: 99%
“…40,54) Significantly, the correlation between esterase activity and the degree of resistance was shown to hold up when an Indian population was selected for increased SP resistance in the laboratory: esterase activity increased in parallel with resistance over the course of selection. 51) Some authors have also suggested that the role of the esterases relative to P450s may have been underestimated in the (many) cases where a contribution from P450s to the resistance has been inferred from synergism data with the P450 inhibitor PBO. This is because H. armigera esterases are also inhibited by PBO.…”
Section: Heliothine Resistance To Spsmentioning
confidence: 99%
“…The association is particularly strong in data for populations from Australia, [39][40][41][42] south and southeast Asia [43][44][45][46][47][48][49][50][51] and central Africa 52,53) and is also significant in Chinese populations, 46,54,55) although it has not been found in west African populations. [56][57][58] Whether this geographic variation in the strength of the associations reflects genetic differences among populations or methodological differences among investigators is moot, although some effect of genetic differences seems likely.…”
Section: Heliothine Resistance To Spsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] reported high level of resistance to fenvalerate and deltamethrin. Tamilselvi [24] , Niranjankumar [25] and Ramasubramanian [26] recently confirmed the high level of resistance to deltamethrin, cypermethrin, lambdacyhalothrin, fenvalerate and beta-cyfluthrin in Tamil Nadu. The resistance development due to exposure of earlier compounds was reported from different parts of India [4,13,15,[27][28][29][30][31][32][33][34][35][36] .…”
Section: Resultsmentioning
confidence: 88%